The Narrators Who Write and Write Not His Hadith in Imam al-Bukhari’s Thua’fa’ Al Sageer: A Comparative Study (Islamic Sciences Journal, 2023)
ABSTRACT          The research deals with the perspectives of the scholars of Al-Jarh and Al-Ta’deel  who are specialized in describing some of the narrators whose narrations of compiled hadith are accepted or modified. The research demonstrates the ultimate accuracy of judging narrators who write and write not hadith. and preserves the knowledge the narrators relied upon and thus transmitted the Sunnah of the Prophet and his companions.  The research is divided into two sections: the first section clarifies the meaning of writing and not writing narration; section two tackles the comparative approach in Thua’fa’ Al Sageer.  The research has two requirements divided between the topic of the narrators who are described as "writing their speech," and the narrators who are not writing”. It relied heavily upon  the perspectives of   Al-Jarh and Al-Ta’deel scholars who preceded Imam Al-Bukhari, as well as those who came later after him.
Keywords: he does not write his hadith. he writes his hadith Thua’fa’ Al Sageer the narrators Al-Bukhari